Carbon starvation following a decade of experimental drought consumes old reserves in Pinus edulis - Peltier, Drew M P (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.